A Facile Strategy to Fabricate Polysaccharide‐Based Magnetic Hydrogel Based on Enamine Bond†. Issue 11 (10th August 2020) - Liu, Hongchen; Yang, Jingru; Yin, Yunlei; Qi, Haisong
Summary of main observation and conclusion: Magnetic hydrogels have found extensive applications in fields such as soft robotics, drug delivery and shape morphing. Here a facile method was fabricated to prepare polysaccharide‐based magnetic hydrogels. The chitosan‐Fe3 O4 ferrofluid was obtained by dispersing carboxyl groups modified Fe3 O4 nanoparticles uniformly in chitosan matrix. Subsequently, the magnetic polysaccharide hydrogel was obtained by simply mixing cellulose acetoacetate solution with chitosan‐Fe3 O4 ferrofluid. The structures and properties of the magnetic hydrogel were analyzed using Fourier‐transform infrared spectroscopy, rheological recovery, responsiveness, and stability measurements. The results indicated that magnetic polysaccharide hydrogel showed pH responsiveness and excellent self‐healing properties, and the hydrogel manifested outstanding stability under physiological conditions (37 °C) for 72 h. In addition, the injectable polysaccharide‐based hydrogel exhibited sensitive magnetic responsive and shape‐shifting ability under an external magnetic field. Therefore, the strategy for the facile preparation of the magnetic polysaccharide‐based hydrogel in this work could provide a benign and versatile method for achieving self‐healing, responsive, injectable properties for the application in biomedical fields. Abstract : A stable magnetic polysaccharide hydrogel based on enamine bond was prepared. The hydrogel showed injectable, pH responsive and excellent self‐healing properties. In addition, the hydrogel exhibited sensitive magnetic responsive and shape‐shifting ability under an external magnetic field, and could combine self‐healing and magnetic properties well.